Modern contraceptive use among reproductive-aged women in Ghana: prevalence, predictors, and policy implications - Paul Beson; Richard Appiah; Augustine Adomah-Afari (BMC, 2018)
Abstract Background Modern contraceptive use remains an important public health intervention and a cost-effective strategy to reduce maternal mortality, avert unintended pregnancies and to control population explosion, especially in developing countries. Despite these benefits, there are reports of low usage among reproductive-aged women in most developing countries. This study examined the prevalence and predictors of use of modern contraceptive among reproductive-aged women in an urban center with a high density population in Ghana. Methods A cross-sectional, interviewer-administered survey was conducted with 217 randomly selected reproductive-aged women. Data was analyzed with STATA. Logistic regression was performed to identify factors influencing modern contraceptive use. Results Although we found high levels of knowledge and awareness (98%; n = 213) of modern contraception use, only 21% of participants were using modern contraceptives. Marital status, partner consent and support, and religious beliefs strongly predicted usage. Conclusion Usage of modern contraceptives among reproductive-aged women in the Ledzokuku Krowor Municipality is lower than the national target. A multilevel family planning intervention program that primarily focuses on promoting inclusive participation of husbands, targets the unmarried and non-literates reproductive-aged women, and dispels misconceptions, misinformation and religious myths about modern contraceptives has been discussed.